Introverts and Extraverts Reflecting on the Experience of Parish Ministry: Conversation Between Training Incumbents and Curates. Issue 1 (2nd January 2016) - Francis, Leslie J.; Smith, Greg
ABSTRACT: Psychological type theory suggests that introverts and extraverts may approach Christian ministry somewhat differently. This theory was tested within the context of a residential workshop attended by 15 curates, 12 of whom were accompanied by their training incumbents. Twelve themes were identified within responses to the question, "What does talk about introversion and extraversion illuminate in the ministry of incumbent and curate and in the life of the parish?" The themes from the perspective of introverts included experiencing and managing tiredness and exhaustion and difficulties experienced dealing with extravert church members. The themes from the perspective of extraverts included reflection and reflective practice, and engagement with others as a source of inspiration.